COMPARISON OF FISH DIVERSITY IN THE OPAK RIVER ECOSYSTEM AND THE INLET OUTLET AREA OF THE GAJAH MUNGKUR RESERVOIR - Kusuma, Aliffia; Putri, Dina Amalia Nova; Nurfitriana, Nindya; Siahaan, Jericho Parsaulian (Jurnal Perikanan Unram, 2024)
Indonesia is a country with high biodiversity. One of these biodiversity riches is fish. Fish diversity in Indonesia can be influenced by different ecosystem conditions. This study aims to determine and compare the diversity of fish species in ecosystems with different conditions. This research was conducted in Kali Opak Yogyakarta and the inlet and outlet areas of Gajah Mungkur Reservoir Wonogiri. Sampling in this study was conducted from April to May 2023. The method used for this research is a survey, fishing and conducting interviews with anglers around the location then the data is analyzed descriptively, namely describing, describing, analyzing the research data obtained, and calculating the index (richness, diversity, and evenness) of each location. The results of this study are, in Kali Opak, Shannon_H value 1.419, Evenness_e^H/S value 1.033, and Margalef value 0.9568. At the WGM Inlet, the Shannon_H value is 1.905, the Evenness_e^H/S value is 0.9596, and the Margalef value is 1.484. Then at the WGM Outlet, the Shannon_H value is 1.292, the Evenness_e^H/S value is 0.9099, and the Margalef value is 0.8656. Differences in fish species were found between Kali Opak and the inlet and outlet areas of Gajah Mungkur Reservoir. Kali Opak has 4 types of fish species, Gajah Mungkur Reservoir inlet has 7 types of species, and Gajah Mungkur Reservoir outlet has 4 types of species. Some species were only found in one study site. Although the inlet has moderate diversity, all study sites have low species richness. The level of species evenness in the three areas is almost the same, indicating an average level of evenness.